2009
DOI: 10.1007/s12519-009-0026-1
|View full text |Cite
|
Sign up to set email alerts
|

Age of puberty in a representative sample of Iranian girls

Abstract: The median age of puberty onset is 10.14 years, and the onset of puberty before 7.5 years is considered as precocious puberty in a representative sample of Iranian girls. The values obtained from the present study can provide baseline data for analysis of time trends, as well as for international comparisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Ethnic differences in the age of onset of puberty have been noted in both girls and boys 56 57. These differences add to the overall variation in pubertal timing when looking at large groups of mixed ethnic background.…”
Section: Pubertal Status and Skeletal Agementioning
confidence: 98%
“…Ethnic differences in the age of onset of puberty have been noted in both girls and boys 56 57. These differences add to the overall variation in pubertal timing when looking at large groups of mixed ethnic background.…”
Section: Pubertal Status and Skeletal Agementioning
confidence: 98%
“…The age range of participants was 11 to 13 years old and their mean age was 12.16 ± 0.74 years. Given that previous studies proposed the age of 12 as the best age for teaching puberty health [31] and considering that the mean age of the onset of menstrual cycle is reported to be 13 years old in Iran [31,32], sixth grade primary school girls were selected as participants. The inclusion criteria were: having had at least three menstrual periods and inclination for participation in the study.…”
Section: Design and Samplesmentioning
confidence: 99%
“…Many studies have shown the earlier onset of puberty especially in girls, but the age of menarche has not significantly changed. Racially different data has been shown in various studies [2][3][4]. Therefore, each country should have its own national reference data for use in clinical practices and for other researches in this area.…”
Section: Brief Communication (Original)mentioning
confidence: 99%